'Getting more comfortable in an uncomfortable space': learning to become an activist researcher in a socially vulnerable sport context. Issue 9 (22nd November 2018) - Luguetti, Carla; Oliver, Kimberly L.
ABSTRACT: Activist research engages all participants as co-researchers in order to challenge the status quo in hopes of creating spaces in which they will actively participate in their education and feel responsible for their own and others' learning. There are a number of challenges that researchers might face when engaging in activist research with co-researchers. In that sense, researchers must be open to multiple perspectives and critical attitudes in order to negotiate the challenges that arise in the process. This paper describes the challenges that the lead author faced in learning to become an activist researcher in a socially vulnerable sport context and how these challenges were negotiated. The lead author, supervised by the second author, conducted a six month activist research study in a soccer program in a socially and economically disadvantaged neighborhood in Brazil. Participants included two researchers (lead and second authors), 17 young people, four coaches, a pedagogic coordinator and a social worker as co-researchers. Multiple sources of data were collected, including 38 field journal/observations and audio records of: 18 youth work sessions, 16 coaches' work sessions, three combined coaches and youth work sessions, and 37 meetings between the lead author and the second author. By using an activist approach four challenges were identified and negotiated: learning to become more comfortable with an activist approach, helping young people to articulate what they know and the researcher to see what they say, valuing co-researchers' knowledge, and negotiating the culture of sport. We argue that challenges are essential, necessary and significant in an activist research project in order to transform ourselves as researchers and our relationship with others.